We need a theoretical framework for the modernization of industrial legacy systems - Garcia, Paulo; Sritriratanarak, Warisa (Frontiers in Industrial Engineering, 2023)
Industrial informatics brings computational intelligence to industry, powering the software-ization of manufacturing processes. However, when faced with the myriad legacy systems that cannot be fully replaced in a cost-effective manner, practitioners must retrofit computational intelligence onto legacy system. This modernization of legacy industrial systems is deceptively challenging: poor retrofitting decisions can cause more harm than good, hindering overall metrics.In this paper, we make the case for the need for a theoretical framework for the modernization of legacy industrial systems. We illustrate the challenge within the context of real-time performance, for the case of industrial cyber-physical systems, depicting a formalization of the problem and illustrating its impact through Monte-Carlo methods. We show how knowledge of extant systems' internals constrain possible optimizations. We conclude by highlighting several research directions, including some recommendations, that must be pursued toward establishing a common theoretical underpinning that can inform practitioners in the field.